Effects of Different Sources of Organic Waste Application on the Growth and Biomass Production of Kenaf (Hibiscus cannabinus L.): Organic Waste Application for Kenaf Growth - Shahariar, Md. Shayeb; Tahsin, Shahrima; Gani, Md. Nasimul; Imamul Huq, Shah Muhammad (Biological Sciences - PJSIR, 2012)